Business Development Strategy Through Enhancement of Resources and Attraction Using The Analytical Hierarchy Process (AHP): A Case Study of RSUD Kota Bogor - Rowi, Roos Farieanna; Ranti, Benny; Rismadi, Bambang; Tarumingkeng, Rudy C. (Master of Management Diponegoro University, 2024)
This research aims to formulate a business development strategy for RSUD Kota Bogor through the enhancement of resources and attractiveness using the Analytical Hierarchy Process (AHP). In the healthcare context, access to quality services is a priority, following the standards established by the World Health Organization (WHO). This study employs a qualitative approach, involving in-depth interviews with management and medical personnel. Analysis results reveal that resources, including financial, human resources, and facilities, as well as attractiveness—comprising customer satisfaction and market factors—significantly influence the hospital's business development. Three main strategies are proposed: development of the hospital as a leading referral institution, establishment of the hospital as a teaching facility, and the implementation of digital services. The findings are expected to provide RSUD Kota Bogor’s management with a guide for developing effective and sustainable strategies